5(y-2)=60

Simple and best practice solution for 5(y-2)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-2)=60 equation:


Simplifying
5(y + -2) = 60

Reorder the terms:
5(-2 + y) = 60
(-2 * 5 + y * 5) = 60
(-10 + 5y) = 60

Solving
-10 + 5y = 60

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 5y = 60 + 10

Combine like terms: -10 + 10 = 0
0 + 5y = 60 + 10
5y = 60 + 10

Combine like terms: 60 + 10 = 70
5y = 70

Divide each side by '5'.
y = 14

Simplifying
y = 14

See similar equations:

| 5k-2=33 | | 3(x+6)=6(2+y) | | 3x+8=-4x-6 | | 4(n+9)-3(2+n)= | | 5(6+n)-2(n-2)= | | 6r+2(r+4)= | | 2+3xy-4xy+6= | | (2x+6)(5x-13)=0 | | x-1.6x-2.6=0.6x+2.2 | | 2(2-x)-4(2x-1)=4(x-1)-3(2x-3) | | 0.33333+x=-0.53333 | | 4.8x+2=3.8x | | 4.8-2=3.8x | | 0.6w+-1w= | | 0.7-(x-2.5)=10.5 | | 13-(-4-x)=1 | | 5.3+9.2x=7.4-8.8 | | 2x+x-12=0 | | 2.3x+6.8=3.94x-3.44 | | 4*(2+x)-2*(x+3)= | | 4d+4=3d+9 | | -(2x-5)=4(x+2) | | 2+3x-(2x+3)= | | 8x+7=2x+10 | | 3x+2(x+10)+3= | | 2*(x+10)= | | (x^4+5x-3)(5x^4-x+2)= | | (x^4+5x-3)-(5x^4-x+2)= | | 3x-7=2x-(3-x+4) | | 4x+34=x/61 | | 4c-3a+5= | | (-x-1)-(x-2)= |

Equations solver categories